(untitled) (Baghdad Science Journal, 2025)
The aim of the study is to assess the risk factors which lead to myocardial infarction and relation to some variables. The filed study was carried out from the 1st of April to the end of Sept. 2005. The Sample of the study consisted of (100) patients in lbn-Albeetar and Baghdad Teaching Hospital. The result of the study indicated the following; 45% of patients with age group (41-50) were more exposed to the disease and there is no significant difference was seen in the level of education, Martial status, weight and height. The result shows that there are significant difference in risk factors like hypertension, cholesterol level in blood and diabetes. When analyzed by T.test at level of P < 0.01 and there are significant difference in smoking habits, hypertension, and diabetes mellitus patient’s when analyzed by chi-squire at level of P < 0.01. The researcher recommends taking the Preventive measuments to control the risk factors.